The misalignment of incentives in academic publishing and implications for journal reform - Jennifer S. Trueblood; David B. Allison; Sarahanne M. Field; Ayelet Fishbach; Stefan D. M. Gaillard; Gerd Gigerenzer; William R. Holmes; Stephan Lewandowsky; Dora Matzke; Mary C. Murphy; Sebastian Musslick; Vencislav Popov; et al. (Proceedings of the National Academy of Sciences, 2025)
For most researchers, academic publishing serves two goals that are often misaligned—knowledge dissemination and establishing scientific credentials. While both goals can encourage research with significant depth and scope, the latter can also pressure scholars to maximize publication metrics. Commercial publishing companies have capitalized on the centrality of publishing to the scientific enterprises of knowledge dissemination and academic recognition to extract large profits from academia by leveraging unpaid services from reviewers, creating financial barriers to research dissemination, and imposing substantial fees for open access. We present a set of perspectives exploring alternative models for communicating and disseminating scientific research. Acknowledging that the success of new publishing models depends on their impact on existing approaches for assigning academic credit that often prioritize prestigious publications and metrics such as citations and impact factors, we also provide various viewpoints on reforming academic evaluation.